Adhesive bond-electromagnetic rivet hybrid joining technique for CFRP/Al structure: Process, design and property. (15th July 2020) - Cui, Junjia; Gao, Song; Jiang, Hao; Huang, Xiaodong; Lu, Guoxing; Li, Guangyao
Highlights: The electromagnetic riveting technique was applied in bond- riveting process. The distribution of adhesive layer thickness after riveting was analyzed. The effects of rivet layout on mechanical properties of CFRP/Al electromagnetic bond-riveted joints were investigated. The bond-riveted joint with four rivets in a square array was proved valuable for actual application. Abstract: In this paper, the effects of rivet layout on mechanical properties of CFRP/Al electromagnetic bond-riveted joints were investigated. Distribution of adhesive layer thickness after riveting was analyzed, and shear tests were carried out. Results showed that the failure of bond-riveted joints was divided into adhesive failure and riveting failure. Bond-riveted joints had considerable shear strengths, and the energy absorption (EA) values of bond-riveted joints were higher than the bonded joint and riveted joints. Among bond-riveted joints, the bond-riveted joint with four rivets in a square array had the highest shear strength, and didn't add too much weight to the joint. Adding rivets to bonded joint changed the distribution of adhesive layer thickness, and provided the anti-shear force anti-peeling moment.